ANNUAL FLOOD ANALYSIS OF CISANGGARUNG WATERSHED IN CIREBON REGENCY - Abdul Muin; Jantiara Eka Nandiasa (NAROTAMA UNIVERSITY, Indonesia, 2019)
Cisanggarung River, a river in West Java Province, often experiences flooding. This study aims to discuss the magnitude of annual flood discharge that may occur in the Cisanggarung watershed. Rain data at each station in the Cisanggarung watershed from 2005 to 2017 were analyzed using descriptive-quantitative methods. Return period flood discharge 2, 5, 10, 20, and 50 years were compared to 2-yearly and monthly flood discharge. The results showed that the data followed the Log-Pearson Type III distribution. The return period flood discharge is: Q2= 181.518 m3/s, Q5 = 242.498 m3/s, Q10 = 283.109 m3/s, Q20 = 316.534 m3/s, Q50 = 373.369 m3/s, Q100 = 412.425 m3/s, Q200 = 452.013 m3/s, dan Q1000 = 546.683 m3/s by using the Nakayasu method. Based on the 2 annual maximum daily rains, 2005, 2007, 2009-2010, 2015, 2009-2017 has the potential to flood Q2, 2012 has the potential to flood Q5, and 2017 has the potential to flood Q10. According to maximum 2-daily monthly rainfall, in 2005-2007, January-April and November have the potential to flood Q2. December has the potential to flood Q10. These results are useful for flood control in the region to be more effective and accurate.